PERUBAHAN KLAUSULA DALAM PERJANJIAN KREDIT AKIBAT FORCE MAJEURE PANDEMI COVID-19 - Difia Fahira Susilo Putri, (2021)
Purpose of this study is to determine whether force majeure can be used as an excuse for changing clauses in the credit agreements and how to credit experienced by debtors due to the COVID-19 pandemic force advanced. This study uses a normative juridical research method, which uses secondary data such as applicable laws and regulations and scientific journals related to the issues under study. The results show that force advanced is one of the factors in the occurrence of bad credit. To save bad credit, debtors can apply for credit restructuring. Credit restructuring may result in changes in clauses regarding rights and obligations that must be obeyed and carried out by both parties due to the renewal of the credit agreement. Settlement of bad credit experienced by debtors due to the Covid-19 pandemic force majeure can be done by restructuring credit as regulated in OJK Regulation Number 48 /POJK.03/2020 concerning Amendments to Financial Services Authority Regulation Number 11 / POJK.03 / 2020 concerning Stimulus National Economy as Countercyclical Policy Impact of Coronavirus Disease 2019 Spread.